Identifikasi Sektor Potensial pada Perekonomian Kabupaten Banjar: Analisis Input-Output - Muhammad Nur Hafizh; M Handry Imansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to determine the potential sectors in improving the economy of Banjar Regency. This study uses input-output analysis to identify potential sectors through the calculation of Forward & Backward Linkage, and Multiplier effects. Input-output table was constructed by deriving Kalimantan Selatan Input-Output Table with an adjustment using Quotient Location. An adjustment using secondary data such as Gross Regional Domestic Product by sectors and by Expenditure, including employment data by sectors in Kabupaten BanjarThe results showed that (1) the processing industry; (2) Transportation, Warehousing and Communication; (3) Finance, Real Estate and Company Services; (4) Electricity, Gas and Water, (5) Construction is a potential sector in Banjar Regency. This sector needs to be developed because expanding this sector is expected to encourage other sectors.The limitations of this research are the limited data obtained and the data used are only the results of documentation by the related agencies.